Examining maternal morbidity across a spectrum of delivery locations: An analysis of the Global Network's Maternal and Neonatal Health Registry. Issue 3 (18th August 2022) - Oberlin, Austin; Wallace, Jacqueline; Moore, Janet L.; Saleem, Sarah; Lokangaka, Adrien; Tshefu, Antoinette; Bauserman, Melissa; Figueroa, Lester; Krebs, Nancy F.; Esamai, Fabian; Liechty, Edward; Bucher, Sheri; et al.
Abstract: Objective: To better understand maternal morbidity, using quality data from low‐ and middle‐income countries (LMICs), including out‐of‐hospital deliveries. Additionally, to compare to the WHO estimate that maternal morbidity occurs in 15% of pregnancies, which is based largely on hospital‐level data. Methods: The Global Network for Women's and Children's Health Research Maternal Newborn Health Registry collected data on all pregnancies from seven sites in six LMICs between 2015 and 2020. Rates of maternal mortality and morbidity and the differences in morbidity across delivery location and birth attendant type were evaluated. Results: Among the 280 584 deliveries included in the present analysis, the overall maternal mortality ratio was 138 per 100 000, while 11.7% of women experienced at least one morbidity. Rates of morbidity were generally higher for deliveries occurring within hospitals (19.8%) and by physicians (23.6%). The lowest rates of morbidity were noted among women delivering in non‐hospital healthcare facilities (5.6%) or with non‐physician clinicians (e.g. nurses, midwives [5.4%]). Conclusion: The present study shows important differences in reported maternal morbidity across delivery sites, with a trend towards lower morbidity in non‐hospital healthcare facilities and among non‐physician clinicians. Synopsis: The analysis provides morbidity estimates on 280 000 pregnancies from six low‐ and middle‐income countries and demonstrates important differences in rates of morbidity across various levels of healthcare provision.